Some Applications of Second-Order Differential Subordination on a Class of Analytic Functions Defined by Komatu Integral Operator. (12th March 2014) - Bulut, Serap
Abstract : We introduce a new class of analytic functions by using Komatu integral operator and obtain some subordination results.